ANALISIS TINGKAT PELAYANAN TERMINAL MENURUT PERSEPSI MASYARAKAT (STUDI KASUS TERMINAL BUKIT SARUNGAN PADANG PANJANG) - Ichsan Harly Pratama; Ishak Ishak; Helga Yermadona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Since the terminal has been operating, significant development has not been carried out so that it causes complicated problems. There are several factors that cause the service at the Bukit Sarungan Padang Panjang terminal to decline, including the presence of damaged roads in the terminal due to flooding, terminal conditions, poor vehicle circulation, the meeting point between incoming and outgoing vehicles. This aims to determine Service Level Analysis. Terminal According to Public Perception (Case Study of Bukit Sarungan Padang Panjang Terminal). The method used is a Likert scale. By distributing questionnaires as many as 92 respondents. This research was conducted by means of a survey through the distribution of respondents' questionnaires. After testing the validity and reliability of the questionnaire, then proceed with data analysis of the research results. From the results of data analysis, the value of the Bukit Sarong Padang Panjang terminal service according to the community with a value of 19% with Very Good Criteria, 47% with Good Criteria, 28% with Poor Criteria. Good and 6% with Bad Criteria. The results of the analysis of 20 respondents obtained the smallest reliability value of 0.621 and the largest reliability of 0.89. This value. While the analysis of 20 people obtained r count with the smallest value of 0.621 > r table with a value of 0.255, it can be said that the data is valid.Keywords: Terminal Service Level, Validity, Reliability, Perception